Production of an Antibacterial Agent, 0-Aminophenol, by a Bacterium Isolated from a Marine Sponge, Adocia sp. - Oclarit, Jose (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
A number of associated bacteria and cyanobacteria in sponges were found to be sources of antibiotics and other bioactive compounds in the marine environment. A purple-colored bacterium was isolated from the body of a marine sponge Adocia sp. The culture of this bacterial isolate produced a substance which inhibited the growth of Staphylococcus aureus and Bacillus subtilis. The substance was purified and consequently identified by various spectrometric methods as o-aminophenol. Moreover, the extract of the host sponge did not contain any antimicrobial activity against those tw9 Gram-positive bacteria.